Propagating Nut Trees - Morrison, Frank D. (My University, 1981)
This publication explains how to propagate nut trees through grafting and budding. Details include supplies, steps and terms to know.
C639_1981_08
Keywords: C639; Lawn and Garden; Forestry; C